Localization of kinesin in cultured cells. - Neighbors, B.W.; Williams, R.C.; McIntosh, J.R. (Journal of Cell Biology, 1988)
Steroid metabolism by different cellular components of preovulatory follicles was studied. Granulosa cells(G), theca cells (T), recombination of granulosa and theca cells (G + T), and cut follicles (F) were isolated from proestrus rats. Each component was then incubated for 3-24h with or without androstenedione (5 X 10(-7) M), 14C-androstenedione or 14C-progesterone. Steroid accumulations were measured by RIA. Metabolites of 14C-steroid were separated by TLC and radioassayed. Estradiol was accumulated in a several fold greater amount in F than in G, T or G + T. In 14C-androstenedione metabolites, testosterone was the major metabolite of G and G + T and 5 alpha-androstane-3 alpha, 17 beta-diol was the second metabolite. Androsterone was the major metabolite of T, and 17 beta-OH compounds were detected in small amounts. Androsterone and 5 alpha-androstane-3 alpha, 17 beta-diol were major metabolites of F. In 14C-progesterone metabolites, 5 alpha-pregnane-3 alpha,20 alpha-diol was the major metabolite of G and G + T after the 24h incubation. 5 alpha-pregnane-3 alpha,20 alpha-diol and 3 alpha-hydroxy-5 alpha-pregnane-20-one were the major metabolites of F, and androsterone was also produced. Smaller amounts of 17 beta-OH and 20 alpha-OH compounds were produced in F than in G + T, and 5 alpha-reduced compound production was considerable. Therefore, 17 beta- and 20 alpha-hydroxysteroid dehydrogenase activity were lower in F than in G + T, and/or 5 alpha-reductase activity was higher in F than in G + T.(ABSTRACT TRUNCATED AT 250 WORDS)